EARLY CHILDHOOD CARE AND EDUCATION INITIATIVES IN INDIA: PROVISIONS AND CHALLENGES - KAUSHAL, SAVITA (THE PRIMARY TEACHER, 2012)
The paper uses a survey of secondary sources and reflection on the existing body of knowledge in the field of early childhood care and education policy and plans. It undertakes a brief review of policy statements on ECCE, exploring the arguments and understanding behind it, and the efforts that have been made. For the purpose of this paper, the term early childhood care and education (ECCE) refers to all programmes where both learning and care occur for children under the age of six (before the start of formal schooling). ECCE or ECE as referred to in the review of studies includes studies on services as regulated child care services (part-day preschools or nursery schools, full-day child care centres and family child care homes) as well as pre-kindergarten programmes and kindergarten that support learning and care